2007
DOI: 10.1086/518894
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin Up‐Regulates the Activity of Double‐Stranded RNA‐Activated Protein Kinase and Enhances the Action of Interferon‐α against Hepatitis C Virus

Abstract: Background. Ribavirin's mechanism of action in the treatment of chronic hepatitis C remains to be clarified. Double-stranded RNA-activated protein kinase (PKR) plays a role in cell defense against virus infection. This study investigated whether PKR is a mediator of the effectiveness of ribavirin, used either alone or in combination with interferon (IFN)-a, against hepatitis C virus (HCV) infection.Methods. Primary human hepatocytes and HCV-replicon cells were treated with ribavirin and/or IFN-a. PKR activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
(37 reference statements)
2
30
0
Order By: Relevance
“…The antiviral function of IFN-␣ depends on direct antiviral actions through transcriptional activation of many ISGs. Two ISGs, encoding OAS and PKR, have been shown to inhibit HCV infection in several studies (26,41,63,66,69,71), and we confirmed their anti-HCV function as described above. We then studied the impact of the Ras/Raf/MEK pathway on these two ISGs.…”
Section: Knockdown Of Raf1 Inhibits Hcv Replicationsupporting
confidence: 87%
“…The antiviral function of IFN-␣ depends on direct antiviral actions through transcriptional activation of many ISGs. Two ISGs, encoding OAS and PKR, have been shown to inhibit HCV infection in several studies (26,41,63,66,69,71), and we confirmed their anti-HCV function as described above. We then studied the impact of the Ras/Raf/MEK pathway on these two ISGs.…”
Section: Knockdown Of Raf1 Inhibits Hcv Replicationsupporting
confidence: 87%
“…6). A previous study reported that reduced eukaryotic initiation factor 2 alpha subunit (eIF2α) phosphorylation was associated with increase in HCV protein synthetic rates and viral RNA replication (32). In addition, DAPK was reported to regulate eIF2-α (33).…”
Section: The Mtor-independent Pathways Might Be Involved In the Antivmentioning
confidence: 99%
“…Although ribavirin on its own exerts a modest antiviral activity (9), its important role in HCV RNA decline and its capability to reduce the emergence of drug resistance suggest a distinct mechanism of action. Thus, the major role of ribavirin in HCV therapy may be immunomodulatory [e.g., by altering the Th1/Th2 ratio toward a more antiviral Th1-dominated immune response (10)(11)(12) and enhancing the IFNinduced gene expression (13)(14)(15)(16)]. …”
mentioning
confidence: 99%